Implementasi Program Pembiasaan Tahfizul Qur’an Dalam Membentuk Karakter Islami di SDIT Assyafiiyah Kabupaten Garut - Noor Raga Putra; Ruslandi Ruslandi; Risal Qori Amarullah (Khidmatussifa: Journal of Islamic Studies, 2023)
After writing and reading activities, al-Qur'an memorization is an important part of Islamic Religious Education learning in schools. Memorizing selected short letters in school, both in elementary and secondary schools, is done in stages based on developmental and educational levels. SDIT Assyafiiyah, Garut Regency, uses the Yaumiyyah Tahfidzul Qur'an program habituation as a supplement to Islamic Religious Education, ensuring that students are proficient not only in knowledge and skills, but also in memorizing the Qur'an. The method used in this study is to use an analytical descriptive method with a qualitative approach, namely, to describe or provide an overview of an object under study through data or samples that have been collected as they are without conducting analysis to make general conclusions. The results of this study are the implementation of Yaumiyyah's Tahfidzul Qur'an habituation at SDIT Asysyafiiyah, Garut Regency. Students are divided into several groups, where this grouping is based on the amount of memorization possessed by each student. The learning evaluation of Yaumiyyah's Tahfizul Qur'an Habituation Program conducted at SDIT Asysyafi'iyah Garut Regency is divided into two times, namely, the daily evaluation is carried out by the teacher when students deposit their newly memorized memorization or deposit their memorized pages by giving an assessment of the reading when memorizing such as makhorijul letters, tajwid, and fluency when depositing memorization, while this semester evaluation is carried out after the end of the school final exam, where each student is required by the teacher to read several letters in accordance with the number of memorization, each individually in front of the teacher. Keyword: Habituation, Tahfizul Qur'an, Yaumiyyah